2015
DOI: 10.1093/cid/civ263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fingerstick Cryptococcal Antigen Lateral Flow Assay in HIV-Infected Persons: A Diagnostic Accuracy Study: Figure 1.

Abstract: When testing 207 people with suspected meningitis by fingerstick with the cryptococcal antigen (CRAG) lateral flow assay, there was 100% agreement with serum or plasma CRAG testing. In 5% of participants, fingerstick testing detected cryptococcal antigenemia in peripheral blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 17 publications
(27 reference statements)
6
84
0
6
Order By: Relevance
“…Available data about urine shows high sensitivity and specificity (JARVIS et al, 2011;PELFREY & BAUMAN, 2012). A recent study that reported 100% agreement between whole blood, serum and plasma LFA results demonstrated that fingerstick CrAg is a reliable bedside diagnostic test (WILLIAMS et al, 2015). Fingerstick LFA seems to be an important and simple tool for the diagnosis of cryptococcal meningitis.…”
Section: Diagnosis Of Cryptococcal Meningitismentioning
confidence: 99%
See 1 more Smart Citation
“…Available data about urine shows high sensitivity and specificity (JARVIS et al, 2011;PELFREY & BAUMAN, 2012). A recent study that reported 100% agreement between whole blood, serum and plasma LFA results demonstrated that fingerstick CrAg is a reliable bedside diagnostic test (WILLIAMS et al, 2015). Fingerstick LFA seems to be an important and simple tool for the diagnosis of cryptococcal meningitis.…”
Section: Diagnosis Of Cryptococcal Meningitismentioning
confidence: 99%
“…The role of lumbar puncture in asymptomatic CrAg+ patients is yet to be defined. Symptoms are not reliable for detection of dissemination to the central nervous system 42 (WILLIAMS et al, 2015). Asymptomatic persons may have CSF positivity, and symptomatic persons may have CSF abnormalities but no diagnostic evidence of Cryptococcus.…”
Section: Screening and Preemptive Treatment For Subclinical Cryptococmentioning
confidence: 99%
“…115 Recently, a lateral flow assay was approved for use in serum and CSF, with sensitivity and specificity of greater than 98% in both specimen types (including whole blood from finger stick samples) and sensitivity of 85% in urine. 116123 The semiquantitative test offers many advantages over the other serologic methods, including rapid turnaround (approximately 15 minutes), minimal requirements for laboratory infrastructure, stability at room temperature, low cost, and wider capture of C gattii polysaccharides. 116 Combined with these advantages, the assay’s excellent performance across a broad range of clinical settings, including settings with low burden of HIV infection and high rates of C gattii infection, 100104 make it an attractive option for point-of-care testing in both resource-available and resource-limited settings.…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Either 40 µL of blood or CSF can determine if cryptococcal disease is present within 10 minutes. 16 It is now feasible for quantitative CSF cultures at baseline to become the mainstay of assessing severity of disease so that appropriate treatment decisions can follow. Baseline CSF quantitative cultures can be readily assessed at 4–7 days after incubation.…”
Section: Discussionmentioning
confidence: 99%